(untitled) (Journal of Hama University, 2026)
The optimal selection of a routing algorithm in on-chip networks enables uniform load balancing across channels. The performance of the routing algorithm implemented in any NoC network primarily determines the achievable QoS values. From this perspective, several issues must be considered when developing new routing algorithms. This includes examining the strengths, weaknesses, and capabilities of existing and popular routing algorithms. This research aims to construct and design an improved routing algorithm that is suitable for the FC-Mesh network architecture and the connectivity nature of it. This algorithm, known as FCM, is then tested for its effectiveness relative to adaptive and deterministic routing algorithms suitable for two-dimensional matrix networks by implicitly invoking these algorithms with the proposed algorithm to study the achievable QoS parameters. Test results showed that the QoS levels achieved by the proposed FCM algorithm on the FC-Mesh topology varied with increasing load. FCM algorithm with deterministic algorithms performed best in terms of throughput and latency, but only at low loads. Meanwhile, FCM algorithm with fully adaptive algorithms demonstrated superior QoS performance at medium and high loads, Partially adaptive algorithms achieved varying quality of service ratios depending on the applied traffic and the injection rate.